Tazkiyatun Nafs as A Strength Base of Teacher Personality Competency - Abdul Ghofar; Usman Abubakar; Muhammad Azhar (Universitas Ahmad Dahlan, 2018)
The teacher should have a steady, stable, adult, wise, and authoritative personality competence, be an example for learners, and have a noble character, but in reality, his personality competence is still low and still far from the personality that teachers should have. The authors offer an alternative solution with the Islamic psychology approach that is Tazkiyatun nafs that can be used as a basis of teacher personality strengthening. This research uses qualitative descriptive approach and literature or library research. The essence of tazkiyatun nafs tends to talk about the soul (an-nafs). It is a process of purification of the human soul from the impurities, both visible dirt and inner dirt. Therefore, the notion of tazkiyatun nafs is closely related to morals and psychology, and in Islam, it serves as a pattern of human formation of good character and cautious to Allah. In this study, the authors found some of the following findings. First, the growth of one's personality is influenced by factors from within that is the integration of elements of aql (mind), qalb (heart), lust and outside factors such as the process of interaction with the environment. Second, the soul is very functional to one's personality. A clean soul will produce good behavior while a dirty soul will result in a low or weak personality.